ISTEC & ISTEC Library Linkage Initiative - De Giusti, Marisa Raquel (2021)
Presentation of the LibLink Initiative (Library Linkages) of ISTEC. The main strategies, projects, and actions carried out in the meeting with the Hermes project are presented.